Effects of a High-Intensity Interval Exercise Programme Using Rope Skipping on Muscular Strength of Undergraduate Students - Phongchin, Wachirawit; Tingsabhat, Suthana; Wongpipit, Waris (An Online Journal of Education, 2022)
The purpose of the study was to examine the effects of a high-intensity interval exercise programme using rope skipping on the muscular strength in undergraduate female students. Twenty-nine undergraduate students participating in the study were divided into three groups: 1) students in a high-intensity interval exercise programme using rope skipping (HIIE) (n=9), 2) students in a moderate-intensity continuous exercise programme using rope skipping (MICE) (n=10), and 3) a control group (no intervention; CONT) (n=10). The experimental groups were asked to perform an exercise for three and five sessions per week, respectively, for 8 weeks. The data were then analysed by comparing the difference of scores by analysis of covariance (ANCOVA) and t-test. The research findings were as follows: 1) the upper-muscular strength in both experimental groups was lower than the baseline (P<.05), 2) the knowledge in both experimental groups was higher than the baseline (P<.05), and 3) the self-efficacy scores between experimental groups were not different. In conclusion, neither the HIIE nor MICE programme using rope skipping improved upper-muscular strength, but they improved the participants’ knowledge of exercise.